Factor structure and psychometric properties of the revised Home Situations Questionnaire for autism spectrum disorder: The Home Situations Questionnaire-Autism Spectrum Disorder. (July 2016) - Chowdhury, Monali; Aman, Michael G; Lecavalier, Luc; Smith, Tristram; Johnson, Cynthia; Swiezy, Naomi; McCracken, James T; King, Bryan; McDougle, Christopher J; Bearss, Karen; Deng, Yanhong; Scahill, Lawrence
Previously, we adapted the Home Situations Questionnaire to measure behavioral non-compliance in everyday settings in children with pervasive developmental disorders. In this study, we further revised this instrument for use in autism spectrum disorder and examined its psychometric properties (referred to as the Home Situations Questionnaire-Autism Spectrum Disorder). To cover a broader range of situations and improve reliability, we prepared seven new items describing situations in which children with autism spectrum disorder might display non-compliance. Parents completed ratings of 242 children with autism spectrum disorder with accompanying disruptive behaviors (ages 4–14 years) participating in one of two randomized clinical trials. Results from an exploratory factor analysis indicated that the Home Situations Questionnaire-Autism Spectrum Disorder consists of two 12-item factors: Socially Inflexible ( α = 0.84) and Demand Specific ( α = 0.89). One-to-two-week test–retest reliability was statistically significant for all scored items and also for subscale totals. The pattern of correspondence between the Home Situations Questionnaire-Autism Spectrum Disorder and parent-rated problem behavior, clinician-rated repetitive behavior, adaptive behavior, and IQ provided evidence for concurrent and divergent validity of the Home Situations Questionnaire-Autism Spectrum Disorder. Overall, the results suggest that the Home Situations Questionnaire-Autism Spectrum Disorder is an adequate measure for assessing non-compliance in a variety of situations in this population, and use of its two subscales will likely provide a more refined interpretation of ratings.